The Role of Trust in Strengthening Repurchase Intention: Evidence from the Business-to-Business Oil and Fats Industry - Ruth Frida Julianti Tambunan; Wendra Hartono (SAFE-Network, 2026)
This study examines the effects of product quality, service quality, and brand image on repurchase intention, with trust as a mediating variable, in the business-to-business (B2B) oil and fats industry. The research was motivated by declining sales performance and increasing customer complaints at PT Multimas Nabati Asahan Serang despite the growth of Indonesia’s palm oil industry. Drawing on the Theory of Planned Behavior, this study proposes that operational and reputational factors shape customer trust and subsequently influence repurchase intention. A quantitative explanatory approach with a cross-sectional survey design was employed. Data were collected from business customers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that brand image significantly affects trust and repurchase intention, while product quality significantly influences repurchase intention. Trust also has a significant positive effect on repurchase intention. However, product quality and service quality do not significantly affect trust, and service quality does not significantly influence repurchase intention. Trust mediates the relationship between brand image and repurchase intention but does not mediate the effects of product quality or service quality. The findings highlight the importance of supplier credibility, reputation, and trust in strengthening customer retention in industrial markets.